Entry to practice physiotherapy students’ use of the international IFOMPT cervical framework to inform clinical reasoning: a qualitative case study design - Katie L. Kowalski; Heather Gillis; Paul Parikh; Katherine Henning; Jackie Sadi; Alison Rushton (BMC Medical Education)
Abstract Background Developing clinical reasoning within entry to practice physiotherapy education is essential to safe and competent practice. For example, identifying the need for referral if the diagnostic process identifies red flags (e.g., serious spinal pathology). The International Federation of Orthopedic Manipulative Physical Therapists (IFOMPT) Cervical Framework supports evidence-based clinical reasoning in assessment and management of the cervical spine region, considering the potential for vascular pathology. Objective To explore the influence of the Framework on clinical reasoning processes of students enrolled in an entry to practice physiotherapy program. Methods The COnsolidated criteria for REporting Qualitative research informed the design and reporting of this qualitative think aloud case study using interpretive description. Participants (students enrolled in an entry to practice physiotherapy program) learned about the Framework through standardized teaching. Clinical reasoning was explored using two cervical spine cases. Elstein’s diagnostic reasoning components and the Postgraduate Musculoskeletal Physiotherapy Practice model guided transcript coding and analysis. Thematic analysis employed a hybrid approach (inductive and deductive) to understand the use of the Framework at key steps in clinical reasoning processes. Multiple strategies enhanced trustworthiness (e.g., regular team debriefs, reflexive engagement). Results For all participants (n = 10), the Framework supported hypothetico-deductive clinical reasoning processes, reflecting a continuum of novice proficiency. The Framework informed generating a vascular hypothesis in the patient history and testing this hypothesis using patient history questions and appropriate physical examination tests. Variable sequences of logic and difficulties with cue interpretation and synthesis were common, leading to a lack of clarity and support for diagnosis and management for some students. Clinical reasoning processes were informed by variable depth and breadth of Framework knowledge and supported by limited personal characteristics (e.g., reflection on action). Conclusions The Framework is a valuable learning resource in entry to practice physiotherapy education to initiate structured clinical reasoning processes for assessing and managing cervical spine presentations, considering the potential for vascular pathology. Owing to a continuum of novice clinical reasoning, using the Framework in entry to practice physiotherapy education requires tailoring to the level of the learner. Future research should explore students’ perspectives of the value of the Framework to inform their clinical reasoning.